The Political Consequences of Unemployment: An Application of the "Power Model" of Blue-Collar Radicalism - Grayson, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
In this article it is argued that in order to be understood, the political attitudes and behaviour of the unemployed must be seen in conjunction with the potential of external organizations to channel the potential discontent resulting from termination. Such an approach is consistent with the 'power model' of blue-collar radicalism. The potential of this approach in understanding the political consequences of unemployment is revealed through a longitudinal analysis of two plant closures in Canada.